MODEL PENCITRAAN POLITIK PAN TAHUN 2009-2014 - ANANG ANAS AZHAR (IAIN Padangsidimpuan, 2017)
This research is assessing the imagery of political model of the Amanat National Party (PAN) on 2009-2014. The political imagery model aims to convince and affecting voters by means of imparting positive opinion to the society on which party imaged. This research used a qualitative approach with descriptive method, and the data collection by using interview, observation and documentation. This research showed some results. First, this party used channel, mass communication, interpersonal communication, and communication beyond the room in order to increase political imagery PAN. Secondly, PAN in Labuhan Batu Selatan did the imagery through the use of the media newspapers, realized their programs as needed by community, as consolidated party, regeneration, attributes, socialization, and the action in the field. The Last model is by using interpersonal communication and did the real programs of PAN in the field